The Effect of Mind Mapping and Semantic Mapping on Reading Comprehension of the Eleventh Graders of Senior High School - Erika Sinambela; Immanuel Padang; Arsen Nahum Pasaribu (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This paper discusses the effect of Mind Mapping and Semantic Mapping techniques on students’ reading comprehension. This research was an experimental quantitative study involving three classes, they were experimental class 1, experimental class 2 and control class. In the experimental classes, the writer applied the Mind Mapping technique and the Semantic Mapping technique while in the control class the method did not apply. The population of this research was students from class XI of Methodist Berastagi. The writer used 105 students as samples; this research sample was taken using random sampling technique. It were about 35 from XI-A class and 35 from XI-B class as experimental class and 35 from XI-C class as control class. To obtain data, the author used a reading test, as an instrument in data collection. This test consisted of two types, namely pre-test and post-test. Based on ANOVA testing P= 0.52 > 0.05 or F count = 7.65 > F table = 2 significantly affected. It can be concluded that the alternative hypothesis (Ha) was accepted while the null hypothesis (Ho) was rejected. Therefore, it can be concluded that Mind Mapping and Semantic Mapping significantly affect the achievement on students’ reading comprehension in narrative text. Based on the explanation above, the writer can choose these techniques as alternatives in learning.